IMPLIKASI UNDANG-UNDANG NOMOR 11 TAHUN 2020 TENTANG CIPTA KERJA BAGI KEMAJUAN INDUSTRI PERTAHANAN INDONESIA (Implication of Law No. 11 of 2020 on Job Creation for the Advancement of Indonesian Defence Industry) - Bernhard Ruben Fritz Sumigar (terAs Law Review : Jurnal Hukum Humaniter dan HAM, 2021)
The superiority of a country in defending its sovereignty and territorial integrity can no longer be directly measured by the amount of military infrastructure it has, however it should also be viewed from the aspect of a country’s ability to build a domestic defence industry that can be useful for meeting national and other countries’ needs. As an effort to develop the defence industry ecosystem in Indonesia, in 2020 the Government of the Republic of Indonesia and the Indonesian House of Representatives enacted Law No. 11 of 2020 on Job Creation (Job Creation Law), one of which regulates the opening of opportunities for the private sector to participate in the development of defence industry sector, thereby automatically changing previous arrangement in Law No. 16 of 2012 on Defence Industry. In this article, the author considers that the changes in the Job Creation Law provisions can bring four advantages to the improvement of the Indonesian defence industry in the future.